Influence of Inclined Magnetic Field, Radiation, and Hall Current on Mixed Convection Flow through an Inclined Channel with Navier-Slip Condition - Reddy, K. Madhusudhan; Kaladhar, K.; Srinivasacharya, D. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we investigate the effects of an inclined magnetic field, Hall current, and radiation on an incompressible mixed convection laminar flow through an inclined channel with slip conditions. Dimensionless governing equations are derived by using the suitable transformations, and the resulting system of ordinary differential equations are solved by using the spectral quasilinearization method (SQLM). The influence of emerging parameters on fluid flow velocities and temperature are presented graphically.